Ex-ante evaluation of investment performance fees using spread options - Dube, Tinashe Alison (Division of Actuarial Science, 2018)
This dissertation analyses ex-ante asymmetric performance fee structures used by South African Mutual Funds and estimates performance fees some time before the fees are paid. Certain parties might benefit from having a reasonable estimate of its value. We use spread option theory to value ex-ante performance fees. The data consist of monthly benchmark and fund gross returns from December 1999 to October 2014. The theoretical value of ex-ante performance fees is a function of spread volatility, therefore high spread volatilities give rise to high ex-ante performance fees. Ex-ante performance fee estimates are highly sensitive to the correlation between the fund and benchmark and a low positive correlation gives rise to a high ex-ante performance fee. The distribution of ex-ante performance fees is positively skewed because of the maximum function in the payoff. Ex-ante performance fee estimates obtained are lower than the actual performance fees paid.